Acidification of potassium acetate and potassium citrate with/without KCl by electro-activation and impact of the solution on spores of Clostridium sporogenes PA 3679 at ambient temperature. (January 2017) - El Jaam, Omar; Fliss, Ismail; Ben-Ounis, Wassef; Aïder, Mohammed
Abstract: Acidity and ORP of electro-activated potassium acetate and potassium citrate with and without KCl was studied and the effect of these solutions on spores of C. sporogenes was evaluated at ambient temperature. The ORP and amount of formed acid were proportional to the intensity of the applied electric current and duration of the electro-activation process. Electro-activation at 400 mA during 60 min yielded solution with ORP values of +417.50 to +1043.33 mV and pH of 3.18–3.47. The four solutions were used to study their effect on spores of C. sporogenes PA 3679 at ambient temperature. The application of electro-activated solutions resulted in a reduction level of >7 log CFU/mL of the spores. The sporicidal effect of the electro-activated solutions was demonstrated by transmission electron microscopy analysis. The micrographs showed several damages in the spores components such as core, coat and spore cortex. Highlights: Electro-activated potassium acetate effective against spores of C. sporogenes. Electro-activated potassium citrate effective against spores of C. sporogenes. Electro-activation as new hurdle approach. Potential for energy saving and minimally processed foods.